Lexeme “if“ in the Conversational Functional styles - Bacić, Cica Z (Sinteze - časopis za pedagoške nauke , književnost i kulturu, 2018)
The subject our interest in this text is the lexeme „if“ and its distribution in the conversational functional style. Our intention is to answer certan questions, where we would emphasize these two: a) can this lexeme be in another class, and b) what is its role in the conversational functional style. In the corpus which is given through written and said forms of the conversational style, we followed the use and their stylish function in the discourse of the everyday conversational and written language. Our research is based on the qualitative analysisof the corpus made of examples which are a reflection of the actual condition in the language. With the description and the analysis of the examples from our corpus, we tried to find its stylish worth in the discourse of the everyday speech, where we emphasize the exponative and ironic function, but our corpus will give examples where the „if“ is a marker of unclear meaning.
Keywords: ironic function; exponative function; style; discourse; conversational functional styles; lexemes